Polysulphide-based Coating for Liquified Petroleum Gas Sensor Improvement - Pauzan, Dr. Mohammad Arif Budiman; Mat Ali @ Yunus, Zalilah Murni; Ruslan, Nurun Najwa; Mohd Zin, Siti Rabaah; Hisamuddin, Nurul Fatihah; Mohammad Shah, Siti Balqis; Wan Sulaimi, Wan Muhammad Faris Hadi (Journal of Science and Technology, 2024)
Sulphur can be found in various applications such as fertilizer, pesticides, cosmetic, etc. However, due to the toxicity and unpleasant odour of sulphur, its use is limited, leading to an abundance of unutilized sulphur especially from petroleum refining process. Therefore, this study intends to apply the unutilized sulphur for other application by developing a polymeric sulphur-based coating for gas sensor enhancement in term of detection of liquified petroleum gas (LPG). The polysulphide coating was fabricated using green strategy-based reverse vulcanization process approach by employing palm oil as a medium for the sulphur modification process with a 10:4:2 ratio of sulphur, epoxy resins, and palm oil, respectively. The analyses of surface morphology and functional group of resulting modified sulphur were characterized by using Scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR) respectively. The sensitivity of prepared modified sulphur as a coated on MQ-6 gas sensor was evaluated and compared to an uncoated gas sensor. The feasibility of the coating was justified where coated gas sensor detects gas at 0.94 seconds while uncoated gas sensor detects at 3.00 seconds which also increased the hydrophobicity to protect the sensor.